2020
DOI: 10.3389/fonc.2020.00268
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding of the Mechanisms Underlying Immune Evasion From PD-1/PD-L1 Immune Checkpoint Blockade in Head and Neck Cancer

Abstract: Starting in 2014, large phase III clinical trials began to disclose the study results of using programmed death (PD)-1 immune checkpoint inhibitors (ICIs) (pembrolizumab, nivolumab) and PD-ligand (L)1 (atezolizumab, durvalumab, avelumab) ICIs immunotherapy in patients with advanced head and neck squamous cell carcinoma (HNSCC). In the recurrent and metastatic (R/M), cisplatin-refractory setting, nivolumab achieved a 2.2-fold increase of the median 1-year overall survival as compared with investigators' choice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 115 publications
(93 reference statements)
2
71
0
Order By: Relevance
“…The serine/threonine kinase Cdk5 has been identified to regulate the PD-1/PD-L1 pathway. Its inhibition confers antitumor immunity due to interference with interferon regulatory factor 2 (IRF2) and interferon regulatory factor-binding protein 2 (IRF2BP2) (66,67). Consistent with this model, the depletion of CDK5 by shRNA leads to the hyperphosphorylation of IRFBP2, increased IRF2 expression, and lower PD-L1 levels (68,69).…”
Section: (V) Cyclin-dependent Kinase 5 (Cdk5)mentioning
confidence: 77%
“…The serine/threonine kinase Cdk5 has been identified to regulate the PD-1/PD-L1 pathway. Its inhibition confers antitumor immunity due to interference with interferon regulatory factor 2 (IRF2) and interferon regulatory factor-binding protein 2 (IRF2BP2) (66,67). Consistent with this model, the depletion of CDK5 by shRNA leads to the hyperphosphorylation of IRFBP2, increased IRF2 expression, and lower PD-L1 levels (68,69).…”
Section: (V) Cyclin-dependent Kinase 5 (Cdk5)mentioning
confidence: 77%
“…Other strategies like adoptive cell transfer or anti-cancer vaccines are limited by reduced T cell activity, the development of autoimmune toxicity or weak immunogenicity [9,10]. Studies revealed that the heterogeneity in the spatial distribution of tumor-infiltrating lymphocytes (TILs), cancer stem cell (CSCs)-related immune invasion and the immunosuppressive microenvironment are the main factors contributing to the lower efficacy of ICB treatment at clinical stage [10,11]. In addition, similarly to the conventional cytotoxic chemotherapy drugs, immunotherapy is constrained by transport processes.…”
Section: Ivyspringmentioning
confidence: 99%
“…HNSCC tumors interfere with the immune system by employing many mechanisms that modulate functions of immune cells to develop immune evasion and immune escape (for more detailed information, please refer to reviews by Albers et al and Qian et al [18,19]). The potential mechanisms for the dysfunction of biological steps in immunity against cancer cells being responsible for the limited response to ICB treatment have been explored in HNSCC [11,[20][21][22][23][24][25][26]. Recently, three tumorimmunophenotypes and related molecular pathways have been recognized according to the spatial distribution of T cells within the tumor microenvironment [23].…”
Section: Immuno-oncology Features Of Hnsccmentioning
confidence: 99%
“…PD-L1 has been utilized not only as a molecular marker of anti-PD-1 therapy, but also as a molecular target for antibody therapy. Anti-PD-L1 mAbs, such as atezolizumab, durvalumab, and avelumab has been used for patients with advanced head and neck squamous cell carcinoma (HNSCC) [ 24 ]. In 45%–87% of OSCC cases, cancer cells were PD-L1 positive, depending on the cut-off value for positivity and whether cytoplasmic staining was included as positive [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-PD-L1 mAbs, such as atezolizumab, durvalumab, and avelumab has been used for patients with advanced head and neck squamous cell carcinoma (HNSCC) [ 24 ]. In 45%–87% of OSCC cases, cancer cells were PD-L1 positive, depending on the cut-off value for positivity and whether cytoplasmic staining was included as positive [ 24 ]. Anti-PD-L1 mAbs have been mainly used for PD1/PD-L1 blockade, but antitumor activities by antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC) against oral cancers have not been investigated.…”
Section: Introductionmentioning
confidence: 99%